Effect of crosslinking density of polymers and chemical structure of amine-containing monomers on the neutralization capacity of dentin adhesives. Issue 10 (October 2015) - Ge, Xueping; Ye, Qiang; Song, Linyong; Spencer, Paulette; Laurence, Jennifer S.
Abstract Objectives Neutralization of the acidic micro-environment at the tooth/material interface is expected to provide enhanced durability for dental composite restorations. The objective of this study is to explore the effect of amine-containing monomer formulations and the crosslinking density of the resultant polymers on the neutralization capacity. Materials and methods The co-monomer system was varied systematically to obtain different proportions of Bisphenol A glycerolate dimethacrylate (BisGMA) and 2-hydroxyethyl methacrylate (HEMA), while maintaining a constant amount of amine-containing methacrylate monomer. A series of amine-containing monomers covering a range of pKa values were examined. Crosslinking density of formed copolymers was controlled by adjusting the weight content of the dimethacrylate monomer BisGMA. Lactic acid (LA) was used as a probe to analyze the effectiveness of the basic polymers to neutralize acid. The neutralization capacity of each amine-containing crosslinked copolymer was characterized by measuring pH as a function of time when the specimens were soaked in 1-mM LA solution, and the results were compared to the control formulations composed solely of BisGMA and HEMA. Polymer surfaces were examined using the methyl orange (MO) assay to quantify the amount of accessible amine groups. Results For each amine-containing crosslinked co-polymer, the neutralization capacity is enhanced by decreasing crosslinking density (e.g., by reducing BisGMA concentration in the formulation). In addition, more amine groups were accessible when crosslinking density was decreased. For different amine-containing polymers with the same BisGMA concentration, the neutralization capacity is higher when the amino monomers with higher pKa values were used in the formulations. Significance This is the first time that the neutralization capacity based on crosslinked dental polymers has been studied. The information is important for future development of durable dentin adhesives.